Analisis Penyertaan Modal Pemerintah Daerah dalam Peningkatan Kinerja Keuangan (Studi Kasus pada Perusahaan Umum Daerah Tirtawening Kota Bandung) - Alfian, Tirta; Apriliawati, Yeti (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to find out how the government's capital participation in an effort to improve the financial performance of Perumda Tirtawening. This research is a qualitative research with a quantitative descriptive approach. The data used in this study are primary data and secondary data obtained by interview and documentation techniques. Data analysis techniques to determine the financial performance of Perumda Tirtawening by calculating using the financial performance formula, namely return on equity, operating ratios, cash ratios, billing effectiveness, and solvency. The results of the research show that the financial performance for 2017-2021 has increased and decreased. The amount of capital investment has no positive effect on ROE, operating ratios, cash ratios, and solvency, while the effectiveness of billing shows an effect.